A rare complication of transcatheter aortic valve replacement: Free-floating nose cone - Derya Tok; Kumral Cagli; Halil Lütfi Kısacık (KARE Publishing, 2019)
Presently described is a case in which the tip of the delivery catheter system (nose cone) has been broken during catheter removal after valve deployment in a femoral transcatheter aortic valve replacement procedure and the successful management of this rare complication.